GAMBARAN ASUPAN ZAT GIZI, STATUS GIZI, DAN PRODUKTIVITAS KERJA PADA PEKERJA PABRIK KELAPA SAWIT BAGERPANG ESTATE PT. PP. LONSUM 2013 - Farah Marlinda Syam; Zulhaida Lubis; Mhd.Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Nutrition intake of worker is one of the important contributing factors in supporting of work produktivity. Fulfillment of nutrients will produce better work productivity. The aim of research to know description nutrient intake, nutritional status and work productivity of worker in the Palm Oil Mill Bagerpang Estate PT. PP. Lonsum 2013. This descriptive reaserch with samples of all worker in the produce  station and workshop station as many as 72 people.The data collected by interview using food recall forms,quetionnairesof work productivity and measure weight and height workers. Result of the research showed that 45.8% workers had energi adequacy levels on normal stage, with an average contribution of energy derived from carbohydrate 67.7%, 20.5% came from fat and 11% from protein. As many as 48,6% of workers had protein adequacy levels on normal stage. Meanwhile more than a half (95,8%) of workers had iron adequacy levels on less category. Nutritional status of workers based on BMI, half of workers (59,7%) had a normal nutritional status and 40,3% workers had nutrition status of over. More than half (69.4%) Bagerpang palm oil mill workers had work productivity on good level and 30.6% workers on enough level. Based on this research suggested to company’s Bagerpang palm oil mill PT. PP. Lonsum especially for health section to give direction or guidance to workers to improve their knowledge about nutrition and conduct nutritional status routine inspection. Keywords : Nutrition Intake, Nutritional Status, Work Produktivity, Factory Workers